Characterization and Identification of Chemical Fungtional Groups in Oyster Mushroom (Pleurotus Ostreatus) Broth with edded Vegetables and Spices - Siti Maulyda Ayu MZ; Halifah Pagarra; Irma Suryani Idris; Oslan Jumadi; Hartati Hartati (bionature, 2023)
Adding the nutritional content of broth powder without destroying the distinctive taste of the broth can be done using pure mushroom extract and additional vegetables and spices. This study aims to determine the organoleptic characteristics and identify the chemical functional groups of glutamic acid in the best samples of oyster mushroom broth powder added with vegetables and spices. The results of the organoleptic test were tabulated in a table and then analyzed using a descriptive test. The organoleptic characteristics of the best color parameters were in treatment B1 which had a pale white color . The best treatment of aroma, texture, and taste parameters were found in the B2 treatment with a characteristic aroma of typical broth, fine powder texture, and has a distinctive taste of broth. The identification of the functional groups of secondary metabolites using the Fourier Transform Infrared (FTIR) instrumentation. Identification results with FTIR showed absorption at wave number (cm-1): 3419.74, 2934.62, 1639.56, 1409.70, 1055.55. There is N-H, O-H, C-H, C=O carbonyl group and carboxylic C-O, which identify the presence of amide compound, phenol acid, alkane, aldehydes, amid I and carboxylic acid, which are known as glutamic acid in this sample. Keywords: Organoleptic, Functional Groups Identification, Oyster Mushroom Broth Powder Why only B1 that you mentioned in color parameters?